พฤติกรรมการแข็งตัวของแท่งโลหะอะลูมิเนียมผสมสังกะสี-แมกนีเซียม-ทองแดง ความแข็งแรงสูงมากพิเศษที่หล่อด้วยกระบวนการหล่อแบบต่อเนื่องภายใต้การประยุกต์ใช้สนามแม่เหล็กไฟฟ้า - เสริมยุทธ แย้มเกตุ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The production of high strength Al-alloy is highly expected especially for the automobile application. A newly developed super high strength Al-Zn-Mg alloy, unfortunately, occurs easily the formation of cracks during solidification, which is so-called hot tearing (internal crack). Its application is severely limited due to the difficulty of obtaining sound ingots of this alloy through conventional direct chill casting (DC). To prevent hot tearing during solidification, fine grain size and minimum thermal stress generated in solidifying ingot are requested. Under a low frequency electromagnetic field, there is a forced convection in the melt during solidification, which results in the formation of finer and uniform grains. In this work the solidification behavior of billet under a low frequency electromagnetic field was investigated. The effect of electromagnetic force on grain refinement was firstly confirmed. Secondly solute redistribution or micro-segregation was measured and microscopic solidification progress was considered to compare the calculation describe solute redistributions which obtained from the assuming of Gulliver-Scheil equation as well as the formation of the smaller eutectic phases, such as α Al+eta(MgZn₂), α Al-eta(MgZn₂)+T(Al-Zn-Mg-Cu) and θ(CuAl₂) were investigated.